The Effect of Halal Label Perception, Lifestyle and Quality of Service on Purchase Decision at Starbucks Coffee in Indonesia - Triwardhani, Diana; Yuliniar; Aswar, Khoirul; Supriyadi, Yudhi Nur (Journal of Economics and Behavioral Studies, 2023)
This study intends to ascertain and assess how Starbucks coffee customers’ perceptions of the halal label, lifestyle, and service quality affect their purchasing decisions. Given that the majority of people in Indonesia are Muslims and that buying a product with a halal label necessitates considering that, as well as the fact that the subject product comes from a non-Muslim nation, this study was conducted. Data were collected from a sample of 252 persons on the island of Java using a questionnaire, and the data were then analyzed using PLS. The results show that the perception of halal labeling, lifestyle and service quality has an impact on purchase decisions. This indicates that the sample used in the study will consume or purchase Starbucks goods if they are halal in compliance with the halal label on the product. Additionally, Starbucks customers tend to be individuals who lead an active lifestyle. Some customers of Starbucks are accustomed to receiving high-quality service along with their purchases; if this trend continues, the sample that will be used in this study won’t purchase Starbucks goods.